Reclamation of Post-Technological Landscapes: International Experience - Lyudmila K. Asyakina; Lyubov S. Dyshlyuk; Alexander Yu. Prosekov (Техника и технология пищевых производств)
Introduction. Anthropogenic activities cause large-scale environmental problems. The growing volumes of toxic emissions contribute to soil, water, and air pollution, thus posing a serious threat to all living systems and the global ecosystem. New reclamation methods are a relevant research topic as they help to restore and preserve ecosystems. Study objects and methods. The research covered sixteen years of scientific publications from PubMed of the National Center for Biotechnology Information (USA), Elsevier (Scopus, ScienceDirect), Web of Science, and the national electronic library service eLibrary.ru. Results and discussion. The authors reviewed various scientific publications to define the main technogenic objects that have a toxic effect on biota. Soil is more vulnerable to destructive effects, and mining wastes are responsible for the largest share of technogenically disturbed objects. Pollutants include many compounds, such as heavy metals, hydrocarbons, sulfur compounds, acids, etc. Reclamation technologies reduce the man-induced impact on the environment, e.g. pollutants can be completely or partially destroyed, processed into non-toxic products, completely removed, stabilized into less toxic forms, etc. This review provides information on the main methods of reclamation of disturbed soils and substantiates the prospect of developing integrated reclamation technologies. Conclusion. The present review featured the main pollutants of anthropogenic origin and the traditional soil reclamation methods. The most prospective new technologies of soil reclamation appeared to be a combination of such biological methods as phytoremediation, bioaugmentation, and biostimulation.